Expression of peroxiredoxin I regulated by gonadotropins in the rat ovary - Lee, Yu-Il; Kang, Woo-Dae; Kim, Mi-Young; Cho, Moon-Kyoung; Chun, Sang-Young (Clinical and experimental reproductive medicine, 2011)
Peroxiredoxins (Prxs) play an important role in regulating cellular differentiation and proliferation in several types of mammalian cells. This report examined the expression of Prx isotype I in the rat ovary after hormone treatment. Immature rats were injected with 10 IU of pregnant mare's serum gonadotropin (PMSG) to induce the growth of multiple preovulatory follicles and 10 IU of human chorionic gonadotropin (hCG) to induce ovulation. Immature rats were also treated with diethylstilbestrol (DES), an estrogen analogue, to induce the growth of multiple immature follicles. Northern blot analysis was performed to detect gene expression. Cell-type specific localization of Prx I mRNA were detected by in situ hybridization analysis. During follicle development, ovarian Prx I gene expression was detected in 3-day-old rats and had increased in 21-day-old rats. The levels of Prx I mRNA slightly declined one to two days following treatment with DES. A gradual increase in Prx I gene expression was observed in ovaries obtained from PMSG-treated immature rats. Furthermore, hCG treatment of PMSG-primed rats resulted in a gradual stimulation of Prx I mRNA levels by 24 hours (2.1-fold increase) following treatment, which remained high until 72 hours following treatment. In situ hybridization analysis revealed the expression of the Prx I gene in the granulosa cells of PMSG-primed ovaries and in the corpora lutea of ovaries stimulated with hCG for 72 hours. These results demonstrate the gonadotropin and granulosa cell-specific stimulation of Prx I gene expression, suggesting its role as a local regulator of follicle development.